Complex of Lascoux in Partition (4,4,4) - Hassan, Haytham (Iraqi Journal of Science, 2023)
In this paper the diagrams and divided power of the place polarization(k )ij  , withits capelli identities have been used, to study the complex of Lascoux in case of thepartition (4,4,4).